Antropometría y adaptación fisiológica en recién nacidos del Hospital Regional de Loreto, enero – junio 2023 - Pasache Pinedo, Piero (2023)
Objectives: To determine the anthropometric measurements and physiological adaptation of healthy term newborns at the Regional Hospital of Loreto from January to June 2023. Methods: Observational, descriptive-correlational, cross-sectional and retrospective study. Results: Female sex predominated in 51.2% and gestational age was 38 weeks in 41.2%. At birth, 92% had a normal weight (mean: 3223.2g; ±SD 422.8g). 78.8% had a normal height (mean: 49.03cm; ±DE 2.04cm). 94.8% had a normal head circumference (mean: 33.6cm; ±DE 1.4cm). According to sex and gestational age, there was statistical significance in the mean difference for the three parameters (p value < 0.05). 41.2% had a heart rate of 150-160lpm (mean: 145.5lpm; ±DE 7.4lpm). In 79.6%, respiratory rate was 50-60rpm (mean: 50.3rpm; ±DE 2.2rpm). In 99.2% the temperature was 36.5-36.9°C (mean: 36.6°C; ±DE 0.1°C). Ninety percent and 96.4% had 8 and 9 Apgar scores at the first and fifth minute, respectively. None of the physiological parameters were statistically significant according to sex and gestational age. Correlation analysis showed that there is a direct relationship between height/heart rate and head circumference/temperature. Conclusions: anthropometric measurements and physiological parameters were determined; and most of the newborns presented these parameters within normal ranges; and a correlation was also found between both parameters.